2021
DOI: 10.48044/jauf.2021.005
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Leaf Thickness, Chlorophyll Content, and Gas Exchange of a Landscape Tree, Xanthostemon chrysanthus, Treated with Paclobutrazol and Potassium Nitrate

Abstract: Paclobutrazol (PBZ)(0 g L-1, 0.125 g L-1, and 0.25 g L-1) and potassium nitrate (KNO3)(0 g tree-1, 100 g tree-1, and 200 g tree-1) were tested on a landscape tree, Xanthostemon chrysanthus (F. Muell.) Benth., in an attempt to enhance its stress tolerance under harsh urban conditions. Significant effects on tree height, diameter at breast height, canopy diameter, leaf area, and anatomy of tree leaves and stems in response to PBZ and KNO3 have been previously reported; in addition to these, the influences on lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The most well-known source of K in the soil minerals such as feldspar and mica although it is found in dust and rainfall likely comes from terrestrial sources [15]. The effects of differences in presence of K in different plants on species' anatomy, morphology, and plant metabolism couldn't be explained yet and they are still debated [16]. It was shown that the presence of K allowed the trees to overcome the stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known source of K in the soil minerals such as feldspar and mica although it is found in dust and rainfall likely comes from terrestrial sources [15]. The effects of differences in presence of K in different plants on species' anatomy, morphology, and plant metabolism couldn't be explained yet and they are still debated [16]. It was shown that the presence of K allowed the trees to overcome the stress conditions.…”
Section: Introductionmentioning
confidence: 99%